Interaction of dietary protein and energy-protein ratio on growth performance of snakehead Channa striata - Hani Wijianti; Muhammad Agus Suprayudi; Nur Bambang Priyo Utomo; Dedi Jusadi (Jurnal Akuakultur Indonesia)
ABSTRACT